Factors influencing the purchasing ability of consumers during the coronavirus pandemic (Journal of Economic Research & Business Administration, 2021)
The aim of the study is to assess various factors affecting consumers when purchasing goods andservices during COVID-19. In today’s constantly changing and highly unpredictable corporate environment,companies and enterprises need to develop a high degree of understanding of the dynamics ofpurchasing behavior and the skills of their customers in order to predict various changes. The studyalso attempted to get consumer opinion on online marketing. a quantitative research methodology wasapplied to collect the opinions of 300 consumers from Almaty and Kostanay regions using a three-partquestionnaire using a reliability test to validate the questionnaire. Based on the current pandemic situation,the authors of this paper initiated a study to examine the dynamics that influenced consumer buyingbehavior in the second quarter of 2020. The selected hypotheses were tested using the Pearson chisquaretest. It is shown that purchasing power is largely influenced by the factors of prices for goods andservices, while other factors such as promotion, salespeople, processes, physical environment have anominal influence on the purchasing behavior of consumers. COVID-19 is the main reason for choosingonline marketing to buy products and services. The results of this study can be useful for both domestic and foreign marketers working in our republic in order to successfully promote products and servicesamong consumers.Key words: purchasing power, consumers, couder-richardson test (kr-20), internet marketing, factors,prices.